Visualisasi data twitter menjadi graph untuk social network analysis - Galih Hendro Martono; Sulistianingsih, Neny (Computer Science and Information Technology, 2023)
Twitter is one of the most widely used social media in Indonesia. As a form of social media, Twitter is widely used to express opinions/opinions, discuss specific issues, convey complaints or sentiments about a product, and political communication. Twitter user communication data can be processed into useful information for various purposes, so we need a way to process Twitter data. The development of information technology makes it possible to multiply this information so that it becomes valuable information. For example, Twitter data can be helpful for companies to profile consumers so that they can improve marketing efforts. In the political field, Twitter data can be used to find people who influence Twitter who can be used to assist the campaign process. In the legal area, this Twitter data can help analyze networks and the distribution of information related to hate speech and hoaxes. To analyze Twitter data, we need to convert it into a data graph to be explored further. Twitter data visualization into data graphs is done because there are differences in data formats. Twitter data is in the form of string data consisting of tweets reflecting user communication. The data graph is a collection of vertices and edges, denoted as Vertex represents Twitter users, and Edge represents user relationships or communication. This study aims to form a data graph based on Twitter data to facilitate the analysis of Twitter data for various interests.